1999
DOI: 10.1002/(sici)1099-1581(199904)10:4<215::aid-pat864>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Bis(arene)chromium-containing polyacrylonitrile and its thermolysis products: synthesis, characterization and magnetic properties

Abstract: Polyacrylonitrile bonded to bis(arene)chromium complexes was prepared by the polycyanoethylation reaction between acrylonitrile and various bis(arene)chromium complexes. The star‐shaped molecules consisted of a central bis(arene)chromium species with up to four polyacrylonitrile arms (each composed of up to 63 acrylonitrile units) covalently bonded to the arene ligands. The products of thermolysis of the polymers at 160°C and 350°C were characterized by elemental analysis as well as infrared nuclear magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Previously, we have found that the treatment of bis(arene)chromium with acrylonitrile gives rise to coordinative polymerization at (arene) 2 Cr 0 , the chain termination step being transfer of an aromatic proton with formation of a bond between the polyacrylonitrile chain and the arene ligand of the chromium complex 6. 7 Here we report that bis(arene)vanadium‐containing polyacrylonitrile can be synthesized in a similar fashion, and that its solutions exhibit outstandingly high third order non‐linear optical properties.…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we have found that the treatment of bis(arene)chromium with acrylonitrile gives rise to coordinative polymerization at (arene) 2 Cr 0 , the chain termination step being transfer of an aromatic proton with formation of a bond between the polyacrylonitrile chain and the arene ligand of the chromium complex 6. 7 Here we report that bis(arene)vanadium‐containing polyacrylonitrile can be synthesized in a similar fashion, and that its solutions exhibit outstandingly high third order non‐linear optical properties.…”
Section: Introductionmentioning
confidence: 95%
“…However, there is evidence for a very significant influence of the polymer matrix on the metal complex, a comparison of the 1 H NMR spectra for CrPAN and (arene) 2 Cr showing a very large shift to low field for the resonances of the aromatic protons (from 4.16 ppm to 7.1-7.5 ppm) (Fig. 3).…”
Section: Synthesis Of Polymer-precursors and Their Spectral Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5] The resulting star-shaped molecules consist of a central (arene) 2 M species with polyacrylonitrile arms covalently bonded to the arene ligands. The properties of thermolysed bis(arene)metal-containing polyacrylonitrile (MPAN) are consistent with the formation of conjugated ladder-type polynaphthyridine structures.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers are closely related to other multi‐component materials, containing completely entangled chains, such as polymer blends, grafts and blocks. Miscibility of the constituent components of the IPNs is a main factor in determining the IPN's morphology .…”
Section: Introductionmentioning
confidence: 99%